Effect of moisture content to the bonding performance of timber-concrete composite beam [electronic resource] - Nur Liyana Aziz, 1989- (2014)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2014